Does individual experience affect performance during cardiopulmonary resuscitation with additional external distractors?. (2nd June 2014) - Krage, R.; Tjon Soei Len, L.; Schober, P.; Kolenbrander, M.; van Groeningen, D.; Loer, S. A.; Wagner, C.; Zwaan, L.
Summary Cardiopulmonary resuscitation is perceived as a stressful task. Additional external distractors, such as noise and bystanders, may interfere with crucial tasks and might adversely influence patient outcome. We investigated the effects of external distractors on resuscitation performance of anaesthesia residents and consultants with different levels of experience. Thirty physicians performed two simulated resuscitation scenarios in random order, one scenario without additional distractors (control) and one scenario with additional distractors (noise, scripted family member). Resuscitation performance was assessed by a score based on European Resuscitation Council guidelines, presented as median (IQR [range]). We found that performance scores were lower under experimental conditions (11.8 (9.0–19.5 [−9.0 to 28.5]) than under control conditions 19.5 (14.0–25.5 [5.0–29.5]), p = 0.0002). No interaction was observed between additional distractors and experience level (p = 0.4480). External distractors markedly reduce the quality of cardiopulmonary resuscitation. This suggests that all team members, including senior healthcare providers, require training to improve performance under stressful conditions.